Africa's Big Five and Other Wildlife Filmmakers : A Centenary of Wildlife Filming in Kenya - Hartley, Jean (Book collections on Project MUSE., 2010)
Jean Hartley, born in Kenya, is acknowledged as being the first to legitimise ìfixingî for wildlife film crews. Over the last 25 years, she has worked on over a thousand films, the vast majority being about wildlife and nature. She features five of the great film makers who all started their careers in Kenya in the1950s, legends whom she is proud to call personal friends. Watching all of their films, and many more, she became fascinated by the history of film making in Kenya and determined to find out when it all started. In this insightful book, she traces the roots of wildlife film back a hu.